The future of online news video - Kalogeropoulos, A; Cherubini, F; Newman, N (Reuters Institute for the Study of Journalism, 2016)
Driven by technological improvements, platform initiatives and investments by media companies, online video news production has exploded during the past years. In this report, we look at how publishers produce online news videos, how they try to monetize it and how audiences consume it. Results show that the supply side is growing at a faster rate from the demand side. Platforms and publishers push online news video, while consumers remain resistant to it. The most successful videos tend to be platform-specific and digital-born outlets are better prepared when adapting to the digital news video grammar than broadcasters and newspapers. In addition, the monetisation of online news video remains the biggest challenge for publishers, given that off-site consumption and soft-news videos dominate the online video landscape. Overall we are cautious about the long-term dynamics for video news.